2021
DOI: 10.5539/gjhs.v13n11p76
|View full text |Cite
|
Sign up to set email alerts
|

Needle Stick Injuries among Health Care Workers in AL-Madinah AL-Munawara Governmental Hospitals in Saudi Arabia

Abstract: BACKGROUND: Needle stick injuries are a dangerous occupational hazard that threatens health care workers with serious consequences in many cases. Because of inadequate reporting of these incidents, the true magnitude of the problem is unknown. The study’s aim was to investigate the epidemiology of needle stick injuries (NSIs) among health care workers in Al Madinah Al Munawara, Saudi Arabia. METHODS: A representative sample of health care workers (n=268) were randomly selected from emer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 20 publications
2
6
1
Order By: Relevance
“…HCWs are exposed to NSIs while performing clinical activities, our findings showed the most common injured group were physicians (36.0 %), nurses (34.8%), dentists (29.2%) and medical technologists (21.1%). Our study findings are in contrast with another study as the injured physician and nurses were found to be higher and injured medical technologists is lower in this study when compared with the study conducted by [12]. In relation to the rate of NSIs among dentists, it is less than its average in neighboring countries such as Jordan (66.5%) [21], whereas 42% in the United Arab Emirates [22] and in 31 countries worldwide, 59.1% of the dentists are exposed to NSIs [9].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…HCWs are exposed to NSIs while performing clinical activities, our findings showed the most common injured group were physicians (36.0 %), nurses (34.8%), dentists (29.2%) and medical technologists (21.1%). Our study findings are in contrast with another study as the injured physician and nurses were found to be higher and injured medical technologists is lower in this study when compared with the study conducted by [12]. In relation to the rate of NSIs among dentists, it is less than its average in neighboring countries such as Jordan (66.5%) [21], whereas 42% in the United Arab Emirates [22] and in 31 countries worldwide, 59.1% of the dentists are exposed to NSIs [9].…”
Section: Discussioncontrasting
confidence: 99%
“…These findings are almost similar to those reported in turkey (20.75%) [15] and slightly lower than that reported in Germany (28.7%) [16] and China (27.5%) [17]. In contrast to our study findings, similar studies conducted in other parts of KSA [13] and Al-Madinah [12] reported slightly higher prevalence of about 29.8% and 32% respectively. Another study conducted in Dammam reports very less prevalence (8.4%) when compared to our study findings [5].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In contrast, the incidence of NSIs among doctors was 24.9% [ 11 ]. Other studies in Saudi Arabia by Albeladi et al (2021) reported 38.4% of nurses [ 32 ] injured from SIs, and Abalkhail et al (2022) reported 34.8% of nurses injured [ 25 ]. An explanation of this could be directly dealing with sharp objects at work, which is significantly associated with the SI experience.…”
Section: Discussionmentioning
confidence: 99%
“…A study done in a few governmental hospitals in the Kingdom of Saudi Arabia (KSA) estimated that the annual NSI incidence was 3.2 per 100 occupied beds, and nurses were the most affected job category [4]. A recent study conducted in a hospital in the Medina region estimated the annual incidence of NSIs among healthcare personnel at 32% [8]. Another study by AlDakhil et al reported that 29.8% of the dental assistants working in private dental clinics in Jeddah, KSA experience at least one event of NSIs since starting their career [9].…”
Section: Introductionmentioning
confidence: 99%